Pharmacokinetic and Pharmacodynamic Modeling of Anidulafungin (LY303366): Reappraisal of Its Efficacy in Neutropenic Animal Models of Opportunistic Mycoses Using Optimal Plasma Sampling - Groll, Andreas H. (American Society for Microbiology, 2001)
The compartmental pharmacokinetics of anidulafungin (VER-002; formerly LY303366) in plasma were characterized with normal rabbits, and the relationships between drug concentrations and antifungal efficacy were assessed in clinically applicable infection models in persistently neutropenic animals. At intravenous dosages ranging from 0.1 to 20 mg/kg of body weight, anidulafungin demonstrated linear plasma pharmacokinetics that fitted best to a three-compartment open pharmacokinetic model. Following administration over 7 days, the mean (± standard error of the mean) peak plasma concentration (C(max)) increased from 0.46 ± 0.02 μg/ml at 0.1 mg/kg to 63.02 ± 2.93 μg/ml at 20 mg/kg, and the mean area under the concentration-time curve from 0 h to infinity (AUC(0–∞)) rose from 0.71 ± 0.04 to 208.80 ± 24.21 μg · h/ml. The mean apparent volume of distribution at steady state (V(ss)) ranged from 0.953 ± 0.05 to 1.636 ± 0.22 liter/kg (nonsignificant [NS]), and clearance ranged from 0.107 ± 0.01 to 0.149 ± 0.00 liter/kg/h (NS). Except for a significant prolongation of the terminal half-life and a trend toward an increased V(ss) at the higher end of the dosage range after multiple doses, no significant differences in pharmacokinetic parameters were noted in comparison to single-dose administration. Concentrations in tissue at trough after multiple dosing (0.1 to 10 mg/kg/day) were highest in lung and liver (0.85 ± 0.16 to 32.64 ± 2.03 and 0.32 ± 0.05 to 43.76 ± 1.62 μg/g, respectively), followed by spleen and kidney (0.24 ± 0.65 to 21.74 ± 1.86 and <0.20 to 16.92 ± 0.56, respectively). Measurable concentrations in brain tissue were found at dosages of ≥0.5 mg/kg (0.24 ± 0.02 to 3.90 ± 0.25). Implementation of optimal plasma sampling in persistently neutropenic rabbit infection models of disseminated candidiasis and pulmonary aspergillosis based on the Bayesian approach and model parameters from normal animals as priors revealed a significantly slower clearance (P < 0.05 for all dosage groups) with a trend toward higher AUC(0–24) values, higher plasma concentrations at the end of the dosing interval, and a smaller volume of distribution (P < 0.05 to 0.193 for the various comparisons among dosage groups). Pharmacodynamic modeling using the residual fungal tissue burden in the main target sites as the primary endpoint and C(max), AUC(0–24), time during the dosing interval of 24 h with plasma drug concentration equaling or exceeding the MIC or the minimum fungicidal concentration for the isolate, and tissue concentrations as pharmacodynamic parameters showed predictable pharmacokinetic-pharmacodynamic relationships in experimental disseminated candidiasis that fitted well with an inhibitory sigmoid maximum effect pharmacodynamic model (r(2), 0.492 to 0.819). However, no concentration-effect relationships were observed in experimental pulmonary aspergillosis using the residual fungal burden in lung tissue and survival as parameters of antifungal efficacy. Implementation of optimal plasma sampling in discriminative animal models of invasive fungal infections and pharmacodynamic modeling is a novel approach that holds promise of improving and accelerating our understanding of the action of antifungal compounds in vivo.